Rancang Bangun Sistem Informasi Penggajian Karyawan Pada UD. NEW SEHATI - Aisyah, Noviani; Tjandrarini, A.B.; Sudharmaningtyas, Pantjawati (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
UD New Sehati is enterprise small middle which active in production and sell may kinds of chips. Payroll system in UD New Sehati calculated based on amount of work day. Overtime calculated based on letter instruction overtime which determined by owner and calculated by hour. Besides that, The employee get bonuses based on the active work employee which assessed from amount of product which has been produced, amount of work day, amount time of delayed and amount of overtime which shown be in the shape of the best value until the worst to make easy the owner give amount of bonuses. Time works for male employee consist or two shifts are morning shift and day shift and nothing overtime. The time work begin at 07.00-16.00 WIB and for day work at 16.00-21.00 WIB. Change shift do every week. Time work for female employee at 07.00-16.00 WIB and nothing shift. Employee presence write by coordinator employeeÂ so that at risk in mistaken in recording. Begin Friday the owner must be count all salary for employee which will be give the employee in Saturday. From some problem happened so that give the solution in the shape of information system payroll employments which can help in storage data employee, make shift schedule, information overtime, letter instruction overtime, storage presence, storage overtime, give bomuses and calculated payroll employee which produce report payroll and report outcome finance for owner andÂ slip salary to employee